Analisis Hukum Pidana Adat Nias Dalam Menyelesaikan Kasus Pencurian - Hepy Krisman Laia (Journal on Education, 2023)
The emergence of customary law and customary sanctions is inseparable from the consequences of a violation or crime, which, according to customary law, is seen as an offense that can disrupt the sense of comfort, tranquility, and peace in communal life. Therefore, the perpetrator of such a violation is subjected to customary sanctions, serving as retribution or a lesson to deter them from repeating the offense. Customary law was implemented by the Dutch on the indigenous people of Indonesia, under the assumption that it was in line with the spiritual atmosphere of the Indonesian society at that time. One component of customary law is customary criminal law, which still exists among communities today, even though the formal Criminal Code has been in place as positive law.